Fiscal Monitor, October 2015 : The Commodities Roller Coaster. (Fiscal Monitor; Fiscal Monitor ;, 2015)
This issue of the Fiscal Monitor examines the conduct of fiscal policy under the uncertainty caused by dependence on natural resource revenues. It draws on extensive past research on the behavior of commodity prices and their implications for macroeconomic outcomes, as well as on extensive IMF technical assistance to resource-rich economies seeking to improve their management of natural resource wealth.